Pelatihan Dua Belas Kompetensi Strategis Generative AI untuk Komunitas Averroes Berdaya - Didin Kristinawati; Eva Nurhazizah; Farah Alfanur (Jurnal Pengabdian Masyarakat Akademisi, 2026)
This community service program aimed to improve AI literacy among young people in Bandung, Indonesia through the framework of the Twelve Strategic Competencies of Generative AI, implemented in collaboration with the Averroes Community involving senior high school and university students aged 15–22 years. Using a participatory, in-class training approach that combined interactive lectures, hands-on practice, case studies, and group discussions, program effectiveness was evaluated through pre-test and post-test instruments, satisfaction surveys, and descriptive statistical analysis using paired sample t-test and Wilcoxon signed-rank test. Results showed a statistically significant improvement in participants' AI literacy after the training (p = 0.003, large effect size), with high satisfaction scores across all evaluated aspects, including material clarity, practical applicability, and facility quality. The integration of technical, ethical, and adaptive competencies enabled participants to move beyond passive AI use toward more critical and responsible engagement, though limitations in sample size and training duration suggest that future iterations would benefit from expanded participation, advanced topic coverage, and integration with soft skills and career readiness training.